Thermodynamic and Voltammetry Investigation of Processes on the Hg3In2Te6 Electrodes Surface - Sema, Oxana; Diichuk, Volodymyr; Kobasa, Igor (Science Signpost Publishing, 2017)
The Hg3In2Te6 electrodes polarisation experiments at acidic, neutral and basic pH values followed by comparison of the experimental data with the results of thermodynamic calculations derived from the Pourbaix diagrams analysis have been used to identify the electrode processes occurring on the Hg3In2Te6 surface and their products. It is proved that the mechanism of the redox processes and qualitative composition of the products formed can be predicted using both voltammetry investigation and the Pourbaix diagram analysis. These results can be useful in planning of the controlled surface modification of Hg3In2Te6.
Keywords: thermodynamic analysis; Pourbaix diagram; voltammetry diagrams; anodic polarization of Hg3In2Te6